2017
DOI: 10.5433/1679-0359.2017v38n4p1987
|View full text |Cite
|
Sign up to set email alerts
|

Fruit agribusiness waste as an additive in elephant grass silage

Abstract: The purpose of this study was to evaluate the potential use of fruticulture waste as an additive in elephant grass (Pennisetum purpureum) cultivar Napier silage at different densities, defining the effect of fermentative quality, microbiological characteristics and bromatological composition. The experimental design was completely randomized with four replications in a 4 x 3 factorial scheme, comprising a control, banana waste (BW), mango waste (MW), and passion fruit waste (PFW) at three densities (400, 500 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…However, this fact did not influence nutrient intake. Furthermore, Van Soest (1994) suggested that NDF intakes above 0.8 to 1.2% LW, as reported in this study, would limit DMI, Figueiredo, M. R. P. et al 1) is close to the 12.20% found by Azevedo et al (2011) but considerably higher than the 7.97% reported by Rogério (2005) and 4.97% reported by Sena et al (2015) and lower than the 20.60% found by Azevedo et al (2017). According to Ferrari et al (2004), the oil extracted from passion fruit seeds has an unsaturated fatty acid content greater than 87%.…”
Section: Resultssupporting
confidence: 70%
“…However, this fact did not influence nutrient intake. Furthermore, Van Soest (1994) suggested that NDF intakes above 0.8 to 1.2% LW, as reported in this study, would limit DMI, Figueiredo, M. R. P. et al 1) is close to the 12.20% found by Azevedo et al (2011) but considerably higher than the 7.97% reported by Rogério (2005) and 4.97% reported by Sena et al (2015) and lower than the 20.60% found by Azevedo et al (2017). According to Ferrari et al (2004), the oil extracted from passion fruit seeds has an unsaturated fatty acid content greater than 87%.…”
Section: Resultssupporting
confidence: 70%
“…Zanine et al (2010) found a similar result, with a reduction in the CP concentration with the addition of cassava scrapings (3.40% CP) in the elephant grass silage. According to Aragão et al (2012) in the mango peel, there is about 3.90% of CP and 3.40% in the pulp, while in the fresh elephant grass there is around 9% at the 90 days of growth (VALADARES FILHO et al, 2018). Therefore, in the present study, the addition of 10.7% of mango residue in elephant grass and cassava peels silage allowed the minimum content of CP (7%), recommended NM: natural matter; 2 SEM: Standard error of mean; 3 L: Linear effect; Q: Quadratic effect; 4 DM: Dry matter; 5 OM: Organic matter; 6 CP: Crude protein; 7 EE: Ether extract; 8 NFC: Non-fibrous carbohydrates; 9 NDF: Neutral detergent fiber; 10 ADF: Acid detergent fiber; 11 MM: Mineral matter.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in the availability of growth factors for forages throughout the year determines the seasonality of forage production, which may compromise animal performance (Mochel Filho et al 2016). Thus, using forage conservation techniques is indispensable to ensure feed supply in sufficient quantity and quality in critical times of the year, highlighting the ensilage technique (Azevedo et al 2017;Guimarães et al 2018).…”
Section: Introductionmentioning
confidence: 99%